2019
DOI: 10.1093/jnen/nlz052
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Findings in Male Patients With Anti-N-methyl-d-Aspartate Receptor Encephalitis

Abstract: Anti-N-methyl-d-aspartate receptor (anti-NMDAR) encephalitis is the most common type of autoimmune encephalitis. The disease predominantly affects women (1:5–1:10), with only 3 reports of autopsy findings in women being published to date. The present study reports findings from the first autopsy performed on a man with anti-NMDAR encephalitis. The patient had some scattered lesions in the limbic system with neuronal loss, gliosis, and microglial activation. The temporal and frontal cortices showed additional p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…While it is well known that the hippocampus is a prime target of anti-NMDAR encephalitis, the ubiquitous expression of NMDA receptors containing the GluN1 subunit in the brain, the manifold symptoms of anti-NMDAR encephalitis and pathologic studies suggest an involvement of most if not all brain regions. 29 Therefore, we think that cerebellum and hypothalamus are valid target regions. In immune cells, we detected colocalization of the genes NR1H3, ACP2, DDB2 , and C11orf49 with eQTL in various immune cells including T-lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…While it is well known that the hippocampus is a prime target of anti-NMDAR encephalitis, the ubiquitous expression of NMDA receptors containing the GluN1 subunit in the brain, the manifold symptoms of anti-NMDAR encephalitis and pathologic studies suggest an involvement of most if not all brain regions. 29 Therefore, we think that cerebellum and hypothalamus are valid target regions. In immune cells, we detected colocalization of the genes NR1H3, ACP2, DDB2 , and C11orf49 with eQTL in various immune cells including T-lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In all, these findings confirm a direct role for antibodies in the pathogenesis of anti-NMDAR encephalitis and, importantly, suggest that neuronal receptor function can recover and result in clinical improvement. Very few autopsy studies of anti-NMDAR encephalitis have been reported, and most of these have involved patients with a short duration of illness ( 63 , 64 ). An as-yet unanswered question is thus whether prolonged neuronal exposure to anti-NMDAR antibodies in affected patients might eventually produce significant neuronal death or irreversible neuronal dysfunction.…”
Section: Pathogenic Mechanisms In Diseases Associated With Antibodies To Neuronal Surface Membrane Antigensmentioning
confidence: 99%
“…1,5 Due to the frequent recovery of patients, neuropathological studies on NMDAR-encephalitis are rare and mainly based on isolated cases with overlapping pathologies or small biopsy specimens, lacking systematic assessment of immune cell infiltration and anatomic correlations. [6][7][8][9][10][11][12][13][14] This study aims to characterize the spectrum of inflammatory changes in different brain areas in patients who have or have not been treated with immunotherapy. Moreover, we describe the overlapping neuropathology of NMDAR-encephalitis with multiple sclerosis (MS)-type demyelination and post-transplant lymphoproliferative disease (PTLD).…”
mentioning
confidence: 99%
“…NMDAR‐encephalitis is characterized by prominent intrathecal production of pathogenic autoantibodies and the reversibility of neuronal dysfunction is reflected by good response to immunotherapy 1,5 . Due to the frequent recovery of patients, neuropathological studies on NMDAR‐encephalitis are rare and mainly based on isolated cases with overlapping pathologies or small biopsy specimens, lacking systematic assessment of immune cell infiltration and anatomic correlations 6–14 . This study aims to characterize the spectrum of inflammatory changes in different brain areas in patients who have or have not been treated with immunotherapy.…”
mentioning
confidence: 99%